RESEARCH ON SINGLE PRESENCE POLICY ON INDONESIA BANKING INDUSTRY (PT. CIMB NIAGA Tbk. CASE STUDY) - AGUNG NGURAH WIRABAWA (NIM : 29107380); Pembimbing: Erman Sumirat, M. Bus, ANAK
This thesis researches, and analyzes the level of success of Bank Indonesia Regulation No. 8/16/PBI/2006 the Single Presence Policy object from the standpoint of regulation, the banks. A valuation of banks subject to Single Presence Policy will be performed to measure success, where the price of company after the merger due to Single Presence Policy will be compared with the price of the company before the regulation issued by the government. Valuations that were used were based on the theory of discounted cash flow valuation, by using a discount factor of the weighted average cost of capital. The instrument used to perform these valuations is risk free rate, default spread, tax rate, risk premium, beta (β), and data - financial data held by companies. Historical data such as the company's financial statements will be used to perform forecasting of asset ownership, debt, income levels, and the level of expenditure. The result of the valuation process is the overall price of the company. Only three banks that will be valuated, PT. Bank Niaga Tbk., PT. Bank Lippo Tbk., And PT. CIMB Niaga Tbk., and one government-owned bank which would be a comparison of the bank charged the Single Presence Policy PT. Bank Mandiri Tbk. As a comparison, similar cases in the Thai banking system will be added to enrich the research. Single Presence Policy Research shows that the results are not in line with government expectations, after the merger, the government hoped that the performance will increased, but the fact that bank rates assessed by the market far below expected values. Single Presence Policy, the regulation that hoped to increase productivity and efficiency has shown a failure. There are sort of ways to evade the failure in Single Presence Policy, such as doing trial process to banks that was targeted to be merged, or in other way, merger or acquisition of shares based on the Single Presence Policy should be done in a longer period, so that banks can do a better preparation.